Permanent disappointment. Graham Greene’s Film Adaptations and Screenplays (1932-1958) - Mancebo Roca, Juan Agustín (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article performs an analysis of the text “The Novelist and the Cinema: A Personal Experience” by Graham Greene, in which the author reflects on the connections between his literature and cinema in 1958. A comparison is drawn between his reflections on the relationship between text and image as a critic and scholar and his film projects and adaptations of his novels. The article concludes that cinema was one of his main references as a novelist and his incursion into the medium increased his literary prestige. However, Greene maintained a deep distrust of the relationship between literature and cinema and its results and was very critical of them. The purpose of this paper is to contribute to the study of Greene by opening new perspectives and debates on the connections between literature and cinema.